Hubungan Kejadian ISPA dengan Status Gizi pada Anak Balita - Ni Ketut Devi Yogiswari; Kadek Ayu Lestari; Anak Agung Gede Indraningrat (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
Acute Respiratory Infection (ARI) is an acute infection in one or more parts of the respiratory tract starting from the nose to the alveolus, including the adnexa (sinuses, middle ear cavity and pleura), where the indications appear for a maximum of 10 days. ARI is a major cause of morbidity and mortality in developing countries, especially children under five. The high prevalence of ARI among toddlers is suspected to be correlated with their nutritional status. This study aims to analyze the correlation of nutritional status with the incidence of acute respiratory infections that attack children under five years, especially 12-59 months in UPT Kesmas Tegalalang II Gianyar during 2019. The study applied a cross sectional analytical approach that took secondary data in the form of 84 records. medical records for children under five at UPT Kesmas Tegalalang II Gianyar in 2019. The medical record data for toddlers was analyzed univariately to see the percentage of the frequency and proportion of each variable and bivariately with chi-square testing to see the effect of nutritional status on ARI cases where the significance value of p <0.05 . The data collected shows that there are 73 children under five with mild ARI (86.9%) and 11 people with moderate-severe ARI (13.1%). Meanwhile, children under five with poor nutritional status were 8 people (9.5%), poor nutritional status 23 people (27.4), good nutritional status 47 people (56%) and over nutritional status 6 people (7.1). %). The results of the bivariate analysis showed a significant correlation between ARI on the nutritional status of children under five (p value = 0.005). This study concluded that there was a significant relationship between ARI and the nutritional status of children under five at the UPT Kesmas Tegalalang II, Gianyar Regency in 2019.